Effect added Black tea residues powder in different proportion To the poultry diet on level of physiological ,hematological , productive trails and antioxidant factor - irhhayym, suhad; Alshemmary, Hind (Journal of Kerbala for Agricultural Sciences, 2021)
The aim of This study was Knowledge of the effect of adding black tea powder residues to poultry diets . in this experiment ,120 birds were divided into three groups ,each group was 4 replicates .The groups were control group (black tea residues powder were not added to the feed ) . first treatment group (added black tea residues powder at a ratio of 60 mg/ kg of feed .second treatment group (added black tea residues powder at a ratio of 160 mg/ kg of feed). Blood samples were collected at the end of the experiment to impose the measurement of P.C.V,( packed cell volume) ,H.b (hemoglobin ) , W.B.C (total white blood cell count ) , R.B.C (total red blood cell account ) ,also calculated cholesterol low density lipoprotein(LDL),high density lipoprotein(HDL) , glucose and the levels of productive characteristic weekly such as average of weight rate ,adequate increase ,the average of feed consumption and the rate of food conversation .then we measured the levels of antioxidant enzymes such asSOD (super oxide dismutase ), MDA(malondialdehyde ) ,CAT (Catalas) , GST (glutathione transferas ) SSH ) ( Glutathion peroxidase ( The result showed that there is significant effect of P≤0.05 added black tea residues powder on the level of antioxidant enzymes ,and ther is effect in lowering of cholesterol , glucose and ther is nois significant effect of P≤0.05 added black tea residues powder on the level of H.b , P.C.V , R.B.C . and W.B.C .